2010
DOI: 10.1021/ac101420f
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on the Optimization of Online Two-Dimensional Liquid Chromatographic Systems Considering Losses in Theoretical Peak Capacity in First- and Second-Dimensions: A Pareto-Optimality Approach

Abstract: A method to optimize different objectives (total analysis time, total peak capacity, and total dilution) has been applied to comprehensive two-dimensional liquid chromatography. The approach is based on Pareto-optimality, and it yields optimal parameters (column particle sizes, column diameters, and modulation times). Losses in the peak capacities in the first dimension (due to undersampling) and in the second dimension (due to high injection volumes) have been taken into account. The first effect (detection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 27 publications
2
125
0
Order By: Relevance
“…This can be achieved by increasing the efficiency of the used columns and reduction of extra-column effects, but most effectively by increasing the number of orthogonal separation dimensions [17]. The principles for the interpretation of these multi-dimensional chromatograms remain the same.…”
Section: Theorymentioning
confidence: 99%
“…This can be achieved by increasing the efficiency of the used columns and reduction of extra-column effects, but most effectively by increasing the number of orthogonal separation dimensions [17]. The principles for the interpretation of these multi-dimensional chromatograms remain the same.…”
Section: Theorymentioning
confidence: 99%
“…Vivo-Truyols et al [18] showed that, under certain circumstances, the loss in peak capacity may reach 75%. It is therefore of crucial importance to find a way to evaluate these correction factors correctly in calculating the effective peak capacity and optimizing LC x LC parameters.…”
Section: Peak Capacity In Lc X Lcmentioning
confidence: 99%
“…2 σv, col is the peak standard deviation in volume units resulting from peak band broadening in the second column, 2 σv, total is the total peak standard deviation in 2 D and CF is the compression factor [30]. CF is related to the two solute retention factors in 2 D, the first one with the 1 D mobile phase and the second one at elution with the 2 D mobile phase [18,30,31]. The compression factor is high if the injection solvent in the transferred fraction is weak.…”
Section: Peak Capacity In Lc X Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…× P cn . Unfortunately, it is difficult to reach the theoretical limits for currently available MDLC systems due to the intrinsic imperfection in orthogonality and some practical limitations such as the unavoidable band broadening caused by dead volumes [3,[12][13][14]. Up to now, various combinations of MDLC have been reported, such as strong cation exchange chromatography -reversed phase liquid chromatography (SCX-RPLC) [15][16][17][18], size exclusion chromatography (SEC) -RPLC [19][20][21], RPLC-RPLC [22][23][24][25], and hydrophilic interaction chromatography (HILIC) -RPLC [26][27][28][29], in either online or offline formats for different proteomics applications.…”
Section: Introductionmentioning
confidence: 99%